Ultrasonography of the late-stage knee osteoarthritis prior to total knee arthroplasty: comparison of the ultrasonographic, radiographic and intra-operative findings - Nevalainen, Mika T.; Kauppinen, Kyösti; Pylväläinen, Juho; Pamilo, Konsta; Pesola, Maija; Haapea, Marianne; Koski, Juhani; Saarakkala, Simo (Scientific reports, 2018)
The purpose of this study was to assess the effectiveness of the ultrasonography (US) on detecting osteoarthritis of the knee, and compare US and radiographic findings to intraoperative total knee arthroplasty (TKA) findings. Fifty-seven late-stage osteoarthritic knees undergoing TKA were evaluated with US and radiography. Standard knee US assessing femoral cartilage damage, osteophytes, effusion, synovitis, and meniscal extrusion was performed. On radiographs, osteophytes, joint space narrowing, and Kellgren-Lawrence grade were evaluated. Corresponding intra-operative findings were assessed during TKA as the gold standard. On the damage of the medial femoral condyle cartilage, the sensitivity of US was high (92%), whereas on the lateral condyle and sulcus area, sensitivities were 58% and 46%, respectively. On osteophytes, the detection rate of the US was remarkable especially on the medial side yielding sensitivities of 90–95%. The sensitivities for detecting effusion and synovitis were also excellent (97%). US detection rate of femoral cartilage damage was in concordance with the radiographic joint space narrowing. For the detection of osteophytes, US provided superior results to radiography particularly on the medial side. In conclusion, US can reliably assess the late-stage OA changes of the knee especially on the medial side of the knee joint.